The Big-bang Strategy and Non-rational Behavior in the Russian Transitional Economy in the 1990s - Rozmainsky, I.V. (Економічний вісник Донбасу, 2015)
The paper offers the following hypothesis: the Big Band (Shock Therapy) strategy of the 1990s in Russia has led to more non-rational behavior of the ordinary Russian people. The point is that in order to make completely rational decisions a person needs avoid both lack of information and information overload. Radical “transition to the market system” by means of the Big Bang strategy had reinforced both these obstacles to rational behavior. On the one hand, radical reforms had increased uncertainty. On the other hand, due to these reforms ordinary Russian people faced with big amount of information which was complex for perception, first of all, on goods and financial markets. The contemporary social, political and economic problems of Russia are concerned, in particular, with low degree of rationality of many its citizens. Roots of it are, among others, in the Big Bang strategy of the 1990s. У статті висувається гіпотеза про те, що стратегія великого поштовху (шокової терапії), яка застосовувалася в 1990-ті роки для реформування російської економіки підвищила ступінь нераціональності поведінки пересічних російських громадян. Справа в тому, що для повністю раціонального прийняття рішень необхідно, щоб людина не стикалася ні з нестачею інформації, ні з інформаційним перевантаженням. Радикальний «перехід до ринку», нав'язаний стратегією великого поштовху, посилив обидві ці перешкоди для раціональної поведінки. З одного боку, радикальні реформи підвищили ступінь невизначеності майбутнього. З іншого боку, ці реформи привели до того, що пересічні громадяни зіткнулися з великою кількістю складної для сприйняття інформації, в першу чергу, на товарних і фінансових ринках. Поточні соціально-політичні та економічні проблеми сучасної Росії пов'язані, зокрема із низьким ступенем раціональності поведінки багатьох її громадян. Коріння цього - в тому числі й в стратегії великого поштовху початку 1990-х років. В статье выдвигается гипотеза о том, что стратегия большого толчка (шоковой терапии), применявшаяся в 1990-е годы для реформирования российской экономики, повысила степень нерациональности поведения рядовых российских граждан. Дело в том, что для полностью рационального принятия решений необходимо, чтобы человек не сталкивался ни с нехваткой информации, ни с информационной перегрузкой. Радикальный «переход к рынку», навязанный стратегией большого толчка, усилил оба эти препятствия для рационального поведения. С одной стороны, радикальные реформы повысили степень неопределенности будущего. С другой стороны, эти реформы привели к тому, что рядовые граждане столкнулись с большим количеством сложной для восприятия информации, в первую очередь, на товарных и финансовых рынках. Текущие социально-политические и экономические проблемы современной России связаны, в частности, и с низкой степенью рациональности поведения многих ее граждан. Корни этого - в том числе и в стратегии большого толчка начала 1990-х годов.